Turkish-Soviet relations (1923-1945) - Al-Agha, عباس محمد جميل; Abadi, فاطمة حمدان (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
Turkish historical studies are of great importance to Turkey's geographical position among the countries of the world and its control of the straits that represent the route of strategic importance of international trade، making it the focus of the attention of European countries، particularly Russia، As relations between the two parties were not at the same pace، punctuated by hostility and tension، This was seen at the beginning of relations، especially before the Republic of Turkey and Russian ambitions to gain a foothold in the Ottoman-controlled Black Sea، It can therefore be said that relations between the two sides have not taken a single quality، but only different qualities at each historical stage.